System Of Information On Data Recording Of Social Assistance Recipients Using Website Technology - Mayasari, Nova; Muslim; Prasetyo, Dimas (Cattleya Darmaya Fortuna, 2024)
The population data collection of social assistance (Bansos) recipients faces various challenges, including data inaccuracy, information duplication, and slow data update processes. These problems can hinder the effective and targeted distribution of Bansos. This study aims to develop a website-based information system that can improve efficiency and accuracy in recording Bansos recipient data. The research methods used include user needs analysis, system design using an iterative software development model, and system testing through field trials. Data were collected through interviews with Bansos management officers and surveys of beneficiaries to ensure the system meets user needs. The results of the study show that this website-based information system is able to facilitate the recording and management of Bansos recipient data more accurately and quickly. This system provides automatic data validation features, real-time data update tracking, and integration with relevant government databases. The implementation of this system is expected to reduce data errors by up to 30% and increase the speed of the data collection process by up to 40%, thus supporting a more effective and efficient distribution of Bansos.